2020
DOI: 10.3390/antib9020026
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Autoimmunity and Biotoxicosis in Sick Building Syndrome as a “Starting Point” for Irreversible Dampness and Mold Hypersensitivity Syndrome

Abstract: Background: The terminology of “sick building syndrome” (SBS), meaning that a person may feel sick in a certain building, but when leaving the building, the symptoms will reverse, is imprecise. Many different environmental hazards may cause the feeling of sickness, such as high indoor air velocity, elevated noise, low or high humidity, vapors or dust. The Aim: To describe SBS in connection with exposure to indoor air dampness microbiota (DM). Methods: A search through Medline/Pubmed. Results and Conclusions: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…DMHS is, therefore, a systemic, low-grade inflammation resulting from exposure to biotoxins. 56 This research also demonstrates that autoantibodies are produced in response to the hypersensitivity induced by dampness, attacking myelin basic proteins and myelin-associated glycoproteins, which contribute to the mitochondrial damage associated with this mouldrelated illness. Studies have shown that neurological issues, most commonly presenting as brain fog, often include reduced cognition, difficulty concentrating and multitasking, and memory impairment.…”
Section: Inflammation and Neurological Symptoms After Mould Exposure ...mentioning
confidence: 78%
“…DMHS is, therefore, a systemic, low-grade inflammation resulting from exposure to biotoxins. 56 This research also demonstrates that autoantibodies are produced in response to the hypersensitivity induced by dampness, attacking myelin basic proteins and myelin-associated glycoproteins, which contribute to the mitochondrial damage associated with this mouldrelated illness. Studies have shown that neurological issues, most commonly presenting as brain fog, often include reduced cognition, difficulty concentrating and multitasking, and memory impairment.…”
Section: Inflammation and Neurological Symptoms After Mould Exposure ...mentioning
confidence: 78%
“…There is evidence linking CI to autoimmunity through autoantibody production against myelin basic protein, myelin-associated glycoprotein, ganglioside GM1, smooth muscle cells, and antinuclear autoantibodies (Abou-donia et al, 2018; Campbell et al, 2010;Gray et al, 2003;Tuuminen, 2020). Other proposed mechanisms for CI involve olfactory-limbic kindling, that is, ampli cation of reactivity to inhaled and ingested chemicals resulting in persistent affective, cognitive, and somatic symptoms (I. R. Bell, 1996; Iris R. Bell et al, 1997;Iris R Bell et al, 1992;Brown-DeGagne & McGlone, 1999).…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…More recently, international research suggests that reversible SBS has the ability to proceed to irreversible hypersensitivity to dampness and/or mouldy indoor conditions that affect many body systems. This is known to present as multiple symptoms and be linked to autoimmunity and such conditions like postural tachycardia syndrome (POTS) and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) [118,119]. The comorbidity of a biotoxin or mould-related illness is also reported to intersect with multiple chemical sensitivity (MCS) [94], tick-borne illness [94] and ME/CFS [59,94] in recent Australian studies.…”
Section: Health Impacts Related To Reported Mould/mildew/fungimentioning
confidence: 99%